2003
DOI: 10.1210/en.2002-220965
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Programming of Reproductive Neuroendocrine Function: Fetal Androgen Exposure Produces Progressive Disruption of Reproductive Cycles in Sheep

Abstract: In the agonadal, androgenized ewe testosterone before birth produces a precocious pubertal rise in circulating LH and abolishes the LH surge mechanism. The present study tested two predictions from this model in the ovary-intact female: 1) prenatal androgen exposure produces early ovarian stimulation; and 2) despite early ovarian stimulation, progestogenic cycles would not occur because of the abolition or disruption of the LH surge. Pregnant ewes were injected with testosterone propionate twice per week from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
110
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 27 publications
5
110
2
2
Order By: Relevance
“…This supports the concept that fetal growth retardation, an early marker of adult diseases, can be initiated through prenatal excess exposure to sex steroids. Studies in nonhuman primates and other animals have shown that prenatal exposure to testosterone led to female hyperandrogenism (19), infertility (22,23), behavior modifications (24) abdominal adiposity (25) and insulin resistance (17) during adulthood in the offspring. In all these studies, testosterone was administered to otherwise normal pregnant female animals and hence the increase in circulating maternal testosterone was of exogenous origin and not caused by any maternal disease.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the concept that fetal growth retardation, an early marker of adult diseases, can be initiated through prenatal excess exposure to sex steroids. Studies in nonhuman primates and other animals have shown that prenatal exposure to testosterone led to female hyperandrogenism (19), infertility (22,23), behavior modifications (24) abdominal adiposity (25) and insulin resistance (17) during adulthood in the offspring. In all these studies, testosterone was administered to otherwise normal pregnant female animals and hence the increase in circulating maternal testosterone was of exogenous origin and not caused by any maternal disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of fetal imprinting, the pubertal activation of sex-specific mating behaviors never occurs [43,116]. Furthermore, not only is puberty important for activational effects of steroid hormones on neonatally imprinted circuits [12,153,16,116,119], but the brain may be sensitive to the organizational effects of steroid hormones during this developmental stage [119,129,39,144]. Matsumoto and Arai showed substantial neural development, as manifested by neurite outgrowth, in the hypothalamus of pubertal animals, and further, that this process was stimulated by exogenous hormone exposure [96,7].…”
Section: Fetal Imprinting and The Maturation Of Adult Sexual Behaviorsmentioning
confidence: 99%
“…This is postulated to be caused by androgen-induced reprogramming of neural development such that GnRH neurons are desensitized to steroid feedback (13,14). Prenatally androgenized (PNA) adult female sheep and primates exhibit elevated LH pulse frequency (13) and irregular reproductive cycles (15,16), evidence of disrupted regulation of the hypothalamic-pituitarygonadal axis. To test the hypothesis that altered fertility in PNA animals occurs by means of a central mechanism at the GnRH neuron, we created a PNA model by using transgenic mice in which GnRH neurons are identifiable by expression of GFP (17), allowing effects of PNA to be studied directly on GnRH neurons.…”
mentioning
confidence: 99%